2006
DOI: 10.1158/1541-7786.mcr-06-0081
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor KLF11 Mediates a Novel Mechanism in Transforming Growth Factor β–Induced Growth Inhibition That Is Inactivated in Pancreatic Cancer

Abstract: c-myc promoter silencing is a key step in epithelial cell growth inhibition by transforming growth factor B (TGFB). During carcinogenesis, however, epithelial cells escape from c-myc repression and consequently become refractory to TGFB-mediated antiproliferation. Here, we assessed the role of the repressor, KLF11, in TGFB-induced growth inhibition in normal epithelial as well as pancreatic carcinoma cells. Endogenous KLF11 was stably down-regulated by RNA interference technology, and the functional consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 41 publications
2
42
0
1
Order By: Relevance
“…Through this key biochemical mechanism KLF11 regulates multiple cellular processes including cell growth, differentiation, apoptosis, endocrine disorders, and malignancy (Buck et al, 2006;Cook et al, 1998;Fernandez-Zapico et al, 2003;Tachibana et al, 1997). Relevant to the current study, we have previously shown that KLF11 (Fernandez-Zapico et al, 2003;Zhang et al, 2001) is a robust transcriptional activator for MAO B (Lu et al, 2008;Ou et al, 2004), increasing the transcription of this gene via distinct GC-rich sites, which are located adjacent to its transcription start sites (Ou et al, 2004).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Through this key biochemical mechanism KLF11 regulates multiple cellular processes including cell growth, differentiation, apoptosis, endocrine disorders, and malignancy (Buck et al, 2006;Cook et al, 1998;Fernandez-Zapico et al, 2003;Tachibana et al, 1997). Relevant to the current study, we have previously shown that KLF11 (Fernandez-Zapico et al, 2003;Zhang et al, 2001) is a robust transcriptional activator for MAO B (Lu et al, 2008;Ou et al, 2004), increasing the transcription of this gene via distinct GC-rich sites, which are located adjacent to its transcription start sites (Ou et al, 2004).…”
Section: Introductionsupporting
confidence: 77%
“…KLF11 is known to inhibit cell growth (Buck et al, 2006;Cook et al, 1998), and increase oxidative stress (Neve et al, 2005) and apoptosis (Tachibana et al, 1997;Wang et al, 2007); which are mechanisms known to contribute to the development and progression of MDD. We hypothesized that KLF11 may be elevated in postmortem brain tissue from subjects with MDD because of the reduced prefrontal cortex volume, signs of cell death, and oxidative damage that have been KLF11-MAO a pathway in chronic stress and depressive disorders S Harris et al reported in the brains of depressive patients (Andreazza et al, 2010;Duman and Monteggia, 2006;Dwivedi et al, 2009), including patients with MDD (Duman and Monteggia, 2006;Dwivedi et al, 2009;Gawryluk et al, 2011;Kang et al, 2007).…”
Section: Upregulation Of the Klf11-mao A Pathway In The Prefrontal Comentioning
confidence: 99%
“…This result suggests that the Myc degradation pathway can be saturated or inhibited by high levels of Myc, explaining why the amplification of the c-myc gene is a powerful oncogenic event (40). On the other hand, Myc is regulated at multiple levels, and it is possible that ca-STAT5A may engage other mechanisms that limit Myc activity, translation, or RNA levels (41)(42)(43)(44)(45). STAT5-induced senescence provides a model system to study the interplay among all Myccontrolling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the functions of Klf10 and Klf11 have been studied in several cells that are TGF-beta-sensitive. Most of these studies have demonstrated that Klf10 and Klf11 mimic the effects of TGF-beta either in promoting apoptosis (Tachibana et al 1997;Ribeiro et al 1999;Bender et al 2004;Wang et al 2007;Jin et al 2007;Gohla et al 2008) or in decreasing proliferation (Cook et al 1998;Hefferan et al 2000b;Fernandez-Zapico et al 2003;Buck et al 2006). The pro-apoptotic effects of Klf10 and Klf11 seem to involve the transcriptional regulation of members of the Bcl-2 family.…”
Section: Role Of Klf10 and Klf11 In Apoptosis And Cell Cycle Progressionmentioning
confidence: 99%